The Effectiveness of Using Minimal Pairs towards Students' Pronunciation Mastery - Bilqisti Rakat; Ika Handayani; Delsa Miranty (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2024)
Pronunciation is essential in communication It can avoid misunderstandings. However, many students have difficulty pronouncing English words. Students in the eleventh grade of SMA Nur El Falah had problems with pronunciation. This research aimed to determine whether minimal pairs is effective towards students’ pronunciation mastery at the eleventh grade of SMA Nur El Falah. This research was located at SMA Nur El in Kubang, Serang District. This research's sample comprised forty-four eleventh-grade students. This research employed a quantitative method using a quasi-experimental with a non-equivalent (Pre-test and Post-test) control group design. The data collecting technique used testing (pre- and post-test), recording, and documenting. The data analysis technique used was statistical calculation analysis using IBM SPSS 25. The findings revealed that minimal pairs was effective towards students’ pronunciation mastery at the eleventh grade of SMA Nur El Falah. It was demonstrated by the value of the Man Whitney-U test that showed 0.000 < 0.05 means alternative hypothesis was accepted. Therefore, this indicated that minimal pairs was effective towards students’ pronunciation mastery at the eleventh grade of SMA Nur El Falah.